Il muschio della memoria. Echi del passato in “Moos auf den Steinen” di Gerhard Fritsch. Con una postilla su Thomas Bernhard (Studia austriaca, 2016)
Gerhard Fritsch’s early novel Moos auf den Steinen (1956) represents a turning point in post-WWII Austrian literature. As other authors did just after the fall of the Habsburg Monarchy, Fritsch outlines the new reality and the legacy his generation inherited from a dissolving past. This essay focuses on the relevance of past memory in Moos auf den Steinen and on the way each character deals with it. Moreover, since Fritsch’s production represents a significant contribution to the poetics of Thomas Bernhard, the last chapter focuses entirely on their personal and professional relationship.